2021
DOI: 10.1177/17411432211006093
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the intellectual lineage of educational management, administration and leadership, 1972–2020

Abstract: This review has two purposes. First, we document the body of knowledge that has accumulated in Educational Management, Administration & Leadership over its five decades of publication. Second, we seek to identify the distinctive contributions of Educational Management, Administration & Leadership as a research journal in educational leadership and management. The review employed the bibliometric method in order to analyze the forms of corpus of 1438 articles published in Educational Management, Adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 83 publications
(181 reference statements)
2
30
0
4
Order By: Relevance
“…EMAL celebrates its 50th anniversary in 2022, an occasion that gives rise to reflect on what has been achieved, what has changed, and where the journal might be going. Such analysis and reflection are presented in the recent review by Hallinger and Kovačevic ́(2021). It follows earlier work by Ribbins (1997) and the 40th anniversary review by Bush and Crawford (2012).…”
Section: Introductionmentioning
confidence: 69%
“…EMAL celebrates its 50th anniversary in 2022, an occasion that gives rise to reflect on what has been achieved, what has changed, and where the journal might be going. Such analysis and reflection are presented in the recent review by Hallinger and Kovačevic ́(2021). It follows earlier work by Ribbins (1997) and the 40th anniversary review by Bush and Crawford (2012).…”
Section: Introductionmentioning
confidence: 69%
“…The overall proportion of critical research, however, is more than previously suggested or found in bibliometric analyses, even where not named as such (e.g. Hallinger and Kovačevic ´, 2021) and reflects the relatively large numbers of primarily American educational-leadership research articles that focus on issues of race.…”
Section: Critical and Functionalist Leadership Researchmentioning
confidence: 86%
“…To our knowledge, no other analysis has compared five snapshots over 50 years. Hallinger and Kovačevic ´(2021), for instance, sample data from a similar range, but analyse it together. We see these contributions as integral to this special issue's celebration of Educational Management Administration & Leadership's 50-year anniversary: our findings locate EMAL as a field leader, publishing diverse as well as important research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veriler içerik analizi ile çözümlenmiş, kod, kategori ve temalar oluşturulmuş ve akran değerlendirmesi ile kontrol edilmiştir. Bu anlamda araştırma, amacı ve sonuçları açısından Hallinger ve Kovačević'in (2019, 2021 EY alan yazınını bibliyometrik açıdan incelediği çalışmalar ile örtüşmektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified